Depression, violence, and socioeconomic outcomes among refugees in East Africa: evidence from a multi-country representative survey - Pozuelo, JR; Bradenbrink, R; Stierna, M; Sterck, O (BMJ Publishing Group, 2023)
Background: Existing research on refugee mental health is heavily skewed towards refugees in highincome countries, even though most refugees (83%) are hosted in low- and middle-income countries. This problem is further compounded by the unrepresentativeness of samples, small sample sizes, and low response rates.